Investing in India : a value investor's guide to the biggest untapped opportunity in the world - Saraogi, Rahul (Hoboken : Wiley, 2014)
A practical, real-world guide to investing in India India's rapid economic growth offers obvious opportunities for foreign investors, but making wise investing decisions can be difficult for any investor without a deep knowledge of the country and its culture. With a vibrant democracy and an active press, India can be a complex and chaotic place in which investors can find it difficult to make investing decisions with confidence. This book offers an on-the-ground perspective on India from one of India's most successful value investors. Looking deeply into the internal realities that impact ...
Preface -- Understanding India -- Government, politics, and the media -- The economy -- Financial architecture -- Afterword -- About the companion website -- About the author -- Index.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: 2000-2099; Investments -- India; Finance -- India; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Finance; Investments; Politics and government; India -- Politics and government -- 21st century; India; Electronic books; Electronic books